Comparative Advantages and Demand in the New Competitive Ricardian Models - Cinquetti, Carlos A. [UNESP] (SAGE Publications, 2018)
We survey the new Ricardian models of bilateral trade, which are seen as tractable structure for multi-country trade models addressing either cost or demand linkages to trade. Cost-based Ricardian models advance new forms of comparative advantages that are irrespective of autarky price and, in some cases, even of opportunity cost. A less noticed feature is their reliance in demand function that does not disturb cost-based prices. Demand-based Ricardian models hinge especially on non-homothetic preferences for asymmetric goods and the supply-side ordering of goods mirrors the demand-side ordering. We also critically discuss extensions of these latter competitive models to trade in quality. We further seek to identify all these models vis-à-vis the Ricardo–Haberler–Deardorff tradition. JEL: F10, 019, D5
Keywords: comparative advantages; demand; multi-country economies; non-homothetic preferences; Ricardian models; trade cost